2001
DOI: 10.1086/318396
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Inner Region of Cygnus X‐1 in the Low/Hard State through Its X‐Ray Broadband Spectrum

Abstract: We present the broadband X-ray spectrum of Cyg X-1 in the low/hard state as observed by the instruments on board BeppoSAX. The spectrum spans from 0.1 to 200 keV, allowing the total accretion luminosity to be observed rather than extrapolated, corresponding to D2% of the Eddington limit for a 10 black hole. The broad bandpass allows us to determine the continuum shape with great accuracy. M _ Simple models of Compton upscattering of seed photons from the accretion disk do not adequately match the spectrum. At … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
161
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(183 citation statements)
references
References 57 publications
22
161
0
Order By: Relevance
“…Their main finding appears that in order to obtain good fits with an expected Fe abundance, A Fe 2, they require certain complexity of the continuum, namely the local spectra close to the BH (which dominate the reflection due to light bending) to be harder than those farther away (which dominate the direct spectrum, especially at low energies). This spectral hardening with the decreasing radius, i.e., following the accretion flow, is fully consistent with a number of other findings, e.g., the presence of hard lags (Kotov et al 2001), spectral variability requiring multiple Compton components, softer at larger radii (Yamada et al 2013), and the concave shape of the ∼1-10 keV continuum of BHXRBs, e.g., Gierliński et al (1997), Frontera et al (2001), Di Salvo et al (2001).…”
Section: Appendix A: Comparison With Previous Spectral Resultssupporting
confidence: 89%
“…Their main finding appears that in order to obtain good fits with an expected Fe abundance, A Fe 2, they require certain complexity of the continuum, namely the local spectra close to the BH (which dominate the reflection due to light bending) to be harder than those farther away (which dominate the direct spectrum, especially at low energies). This spectral hardening with the decreasing radius, i.e., following the accretion flow, is fully consistent with a number of other findings, e.g., the presence of hard lags (Kotov et al 2001), spectral variability requiring multiple Compton components, softer at larger radii (Yamada et al 2013), and the concave shape of the ∼1-10 keV continuum of BHXRBs, e.g., Gierliński et al (1997), Frontera et al (2001), Di Salvo et al (2001).…”
Section: Appendix A: Comparison With Previous Spectral Resultssupporting
confidence: 89%
“…Also, it is important to note that observational support to the existence of cool inner discs in hard state black hole X-ray binaries has been claimed for a several systems (Di Salvo et al 2001;Miller et al 2006;Reis, Miller & Fabian 2009;Reis, Fabian & Miller 2010), albeit Tomsick et al (2009) have shown that the inner disc in GX339-4 recedes sharply below 1 per cent of the Eddington luminosity, i.e. over the luminosity range where this system exhibits a remarkably tight non-linear correlation however, see, e.g., D'Angelo et al 2008 andKolehmainen, Done &Díaz Trigo 2014 for a different interpretation of the soft X-ray excess).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…At a distance of few times 10 11 cm (see also Romero et al 2014), the energy density of the stellar radiation field (ω ) becomes dominant with respect to the other two photon fields. In particular, ω = L /4π(R 2 orb + Z 2 )c, where L =7×10 39 erg s −1 is the star luminosity (Orosz et al 2011), R orb is the orbital distance assumed to be 3×10 12 cm, and Z is the distance from the BH along the jet, whereas ω synch = L MeV tail /4πZ 2 c and ω accretion = L so f tXray /4πZ 2 c, with L so f tXray the luminosity in the 1-20 keV energy range spanning from 10 36 to 2 × 10 37 erg s −1 , depending on the model used to fit the soft part of the spectrum (Di Salvo et al 2001). Particles could also be accelerated outside the binary system in shocks formed when the jets interact with the surrounding medium, as it is likely to be the case in the microquasar SS 433 (Bordas et al 2015).…”
Section: Discussionmentioning
confidence: 99%